(untitled)
Processing conditions are important in the quality and preservation of meat of various kinds and sources. Frying is one of the processing techniques often employed in meat products, snail meat inclusive. This study evaluated the effect of deep frying on the polycyclic aromatic hydrocarbon, textural, thermal, and nutritional properties of African snail meat. Fasted snails were processed and deep-fried at varying time intervals (0, 4, 8, 12, and 16 minutes) before retrieval for analysis. The polycyclic Aromatic Hydrocarbons (PAHs) of deep fried African snails at varying times revealed that Naphthalene, Acenaphthylene, Acenaphthene, Fluorene, Phenanthrene, Anthracene, Fluoranthene, Pyrene, Benzo(a)anthracene, Chrysene, Benzo(b)fluoranthene, Benzo(k)fluoranthene, Benzo(a)pyrene, Indeno(1,2,3–cd